SATIRE IN THE WORK OF NODIM NAMANGANI POETICAL PERFECTION (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the poetic development and artistry of satire in Uzbek literature using the example of Nodim Namangoniy's work. In the poet's work, such poems as “Travelogue”, “Bezgak”, “Ehtiyozh”, “Galati”, “Khit Khoddi” and the Persian-Tajik rubaiyats included in “Travelogue”, such vices as injustice, ignorance, bribery, and injustice in society are revealed. The article substantiates the socio-philosophical essence of the poet's satire, its manifestation as an artistic force that awakens a person through ironic imagery and laughter.